2002
DOI: 10.1038/modpathol.3880551
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic PTEN/MMAC1 Loss of Heterozygosity in Conventional (Clear-Cell) Renal Cell Carcinoma is Associated with Poor Patient Prognosis

Abstract: As a group, renal epithelial malignancies are frequently encountered in clinical practice. It is now appreciated that rather than being a single tumor type, they consist of a variety of morphotypes that show differing clinical behavior (1-3). The most frequently encountered subtype is conventional (clear cell) renal cell carcinoma (cRCC), representing 70% of all adult malignant primary renal tumors, whereas papillary renal cell carcinoma (pRCC) account for 10 -15%, and chromophobe renal cell carcinoma (chRCC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 24 publications
1
46
0
1
Order By: Relevance
“…It was recently reported that loss of one copy of a gene without any alteration in the remaining wild-type allele, a phenomenon referred to as haploinsufficiency, may be sufficient to promote cancer in many instances. Such is the case with the PTEN gene in solid renal cell carcinomas (Velickovic et al, 2002), SMAD4 in gastric cancers (Xu et al, 2000;Maurice et al, 2001) and p27 in various other cancers (Fero et al, 1998;Philipp-Staheli et al, 2001). Our data raise the possibility that haploinsufficiency of PTC may be involved in early UC, at least in tumours with LOH of the PTC marker.…”
mentioning
confidence: 52%
“…It was recently reported that loss of one copy of a gene without any alteration in the remaining wild-type allele, a phenomenon referred to as haploinsufficiency, may be sufficient to promote cancer in many instances. Such is the case with the PTEN gene in solid renal cell carcinomas (Velickovic et al, 2002), SMAD4 in gastric cancers (Xu et al, 2000;Maurice et al, 2001) and p27 in various other cancers (Fero et al, 1998;Philipp-Staheli et al, 2001). Our data raise the possibility that haploinsufficiency of PTC may be involved in early UC, at least in tumours with LOH of the PTC marker.…”
mentioning
confidence: 52%
“…37,38 Reduced PTEN protein expression has been found in a high frequency in RCC and is associated with PKB/Akt activation in ccRCC, but interestingly not in pRCC. 2,39 The collected data suggests that in ccRCC the PTEN directed regulation of the PI-3 kinase pathway is affected by both genetic aberrations in the PTEN gene and by DJ-1 gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of mTORC1 inhibitors, particularly temsirolimus, in renal cell cancer has raised the possibility that responders share a common molecular phenotype that renders these tumours dependent on mTOR for growth and/or survival. In renal cell cancer, PTEN gene expression has been shown to be downregulated in a large percentage of cases, presumably by epigenetic silencing (Brenner et al, 2002;Velickovic et al, 2002). In particular, lack of PTEN expression has been shown to be an independent negative prognostic factor for diseasespecific survival in patients with metastatic renal cell carcinoma (Kim et al, 2005).…”
Section: Differential Review Of Biological Effects Of Mtor Inhibitionmentioning
confidence: 99%